Distributions and stable carbon isotopic compositions of biomarkers in torbanites from different palaeogeographical locations - Grice, Kliti; Audino, Michiele; Alexander, Robert; Kagi, Robert (Elsevier Science, 2001)
The relative distributions and stable carbon isotopic compositions of certain aliphatic and aromatic biomarkers from 11 Botryococcus braunii rich torbanites from Scotland, South Africa and Australia covering the Late Carboniferous to Late Permian were investigated. The data was scrutinised for any evidence of molecular features which may be characteristic of palaeogeography. The torbanites studied were selected to cover a range of age and palaeoclimatic conditions (e.g. Permian and Late Carboniferous when Gondwana was covered by an extensive ice sheet, the Late Permian when the climate warmed from glacial to cool to temperate and the Carboniferous when Laurasia was located within the equatorial zone). All torbanites are composed of abundant n-alkanes and novel macrocyclic alkanes which, based on similar d13C values, are ascribed a common origin. All samples are also characterised by a high cyanobacterial input as indicated by abundant hopanoids. Other biomarker distributions and stable carbon isotopic compositional differences separated the torbanites into three groups, which also correlate to three different palaeogeographical/palaeoclimatic precincts: (i) Group A?southern Africa and eastern Australia (Temi) torbanites which are characterised by a high relative abundance of cyanobacterial and methylotrophic hopanoids, abundant branched hydrocarbons and 13C enriched homologous series of monomethylakanes; (ii) Group B?eastern Australia (Newnes and Glen Davis) torbanites contain relatively high amounts of drimanes and abundant 13C enriched homologous series of monomethylakanes; and (iii) Group C?Scottish torbanites (Torbane Hill and Westfield) contain high relative amounts of cyanobacterial hopanoids, methylotrophic hopanoids and abundant branched aliphatics (but no 13C enriched homologous series of monomethylakanes).